KULIAH KERJA NYATA: MENGGALI POTENSI BUDAYA DAN EKONOMI LOKAL DESA TUGUMUKTI - Rohadatul Aisy, Zahra; Insani, Nurul Alfiah; Maha Dewi, Aura Pridita; Susanti, Susi; Maryati; Nur Ramdan, Rahmat (Jurnal Istimā, 2024)
This research aims to explore and optimize the potential of local culture and economy in Tugumukti Village as an effort to support local development and improve community welfare. The research uses a descriptive qualitative method with data collection techniques through in-depth interviews, observations, and documentation. The results of the study revealed that Tugumukti Village has various local economic potentials, such as the Al-Barokah Lemon Farmers Group which has grown rapidly as one of the main sources of income for the community. In addition, this village has natural tourist attractions such as Cipalasari Waterfall, Ogoh-Ogoh cultural traditions in commemoration of Independence Day, and the Milangkala Village festival. However, the development of village potential faces obstacles such as the lack of infrastructure and supporting facilities. By strengthening local institutions, optimizing the use of technology, and improving infrastructure, the cultural and economic potential of Tugumukti Village can be maximized to support inclusive and sustainable development. The Community Service Program (KKN) serves as a means for students to apply knowledge in the form of community service, as well as contribute to the exploration and development of village potential.